Bioactive secondary metabolites from the Borneon soft corals of the genus Nephthea - Ishii, Takahiro; Ueoka, Reiko; Matsunaga, Shigeki; Vairappan, Charles S. (Malaysian Journal of Science, 2010)
As part of our continuous interest in the presence of secondary metabolites in marine organisms of Borneo, we investigated the chemical constituents of the soft corals of the genus Nephthea. Four secondary metabolites were isolated from the organic extracts of three Borneon soft corals Nephthea species and these compounds were identified as 24-methylenecholesterol (1), 50,41-epidioxy-11-hydroxy-6-eudesmene (2), 5beta,8beta-epidioxy-11-hydroperoxy-6-eudesmene(3)and24-methyl-cholesta-5,24(28)-diene-3beta,19-dio1-7beta-monoacetate (4). Their structures were established by NMR spectroscopic data analysis and comparison of the data with those of the literature.